Association Between Green Rural Road Elements and Socioeconomic Development Indicators in Rural Areas - Mustafa, Nur Ainina; Munikanan, Vikneswaran; Zakaria, Rozana; Abd Rashid, Mohamad Hafizuddin Syafiq (International Journal of Sustainable Construction Engineering and Technology, 2025)
Sustainable development is defined as the development that meets the needs of the present without compromising the ability of future generations. In Malaysia, particularly in rural areas, the networks comprise the largest proportion of roads in the country, making efficient road development critical for economic progress. However, such development has significantly impacted the environment, contributing to substantial ecological disruption and affecting the quality of life in local communities throughout the road lifecycle. Therefore, the adoption of sustainable approach by implementing green elements in the development and operation of rural road infrastructure is the ideal way forward to concurrently meet economic, social and environmental needs. Accordingly, this study seeks to identify the green rural road elements that should be considered in the development of rural roads. It also investigates which green elements can potentially contribute to socioeconomic development in rural areas. A quantitative method was employed, using a questionnaire survey as the research instrument to determine the significant green rural road elements. Data collection was conducted using the census method, resulting in the return of 63 completed questionnaires. The data were analyses using Goodman Kruskal’s Gamma. The analysis revealed that seventeen (17) green rural road elements were statistically significant and showed a strong positive association with at least one of the socioeconomic development indicators studied. These proposed elements are expected to enhance stakeholder understanding and offer practical guidance for improving the sustainability of rural road infrastructure projects. Ultimately, this contributes not only to environmental conservation but also to the advancement of social and economic well-being in rural communities.